The Impact of Management by Walking Practice on the Effectiveness of Strategic Decisions in Jordanian Industrial Corporations Companies - Al-Dalain, Ali (Jordan Journal of Business Administration, 2015)
This study aimed to identify the impact of management by walking practice on the effectiveness of strategic decisions in Jordanian industrial corporations companies. To achieve this objective a questionnaire was developed and distributed to the sample of the study which consisted of (327) respondent. The Statistical Package for Social Sciences (SPSS) was used to analyze the collected data. The study has reached the following results : There is an impact of management by walking practice in the dimensions of effectiveness of strategic decisions which explains (68.7%) of variation in the dependent variable (the effectiveness of strategic decisions). The study concluded a set of recommendations was the most important: that the Jordanian industrial corporations companies to enhance the degree management by walking practice, through a training and educational courses to improve the effectiveness of strategic decisions.